Sensitivity of Charitable Giving to Realized Income Changes: Evidence from Military Bonuses and the Combined Federal Campaign - Carl J. Wojtaszek; Michael S. Kofoed (Institute of Labor Economics (IZA), 2021)
The permanent income hypothesis states that agents perfectly smooth consumption given a large, anticipated shock to income. Testing these implications is difficult given the endogenous nature of income and payment timing. We leverage exogenous variation in military bonus size and timing matched with donations from a large workplace charitable drive where soldiers contribute via payroll deductions during a fixed open enrollment period. Our findings suggest that soldiers are 5 to 10 percent more likely to contribute if they receive their bonus during the open enrollment period. We show that soldiers smooth donations more with age and increased bonus experience.
Keywords: D9; D64; H31; 330; charitable giving; altruism; income shocks; permanent income hypothesis